Ecotoxicology and geostatistical techniques employed in subtropical reservoirs sediments after decades of copper sulfate application - Biamont-Rojas, Ivan Edward [UNESP]; Cardoso-Silva, Sheila; Bitencourt, Marisa Dantas; Santos, André Cordeiro Alves dos; Moschini-Carlos, Viviane [UNESP]; Rosa, André Henrique [UNESP]; Pompêo, Marcelo (Springer Nature, 2022)
Spatial distribution linked to geostatistical techniques contributes to sum up information into an easier-to-comprehend knowledge. This study compares copper spatial distribution in surface sediments and subsequent categorization according to its toxicological potential in two reservoirs, Rio Grande (RG) and Itupararanga (ITU) (São Paulo—Brazil), where copper sulfate is applied and not applied, respectively. Sediments from 47 sites in RG and 52 sites in ITU were collected, and then, copper concentrations were interpolated using geostatistical techniques (kriging). The resulting sediment distributions were classified in categories based on sediment quality guides: threshold effect level and probable effect level; regional reference values (RRVs) and enrichment factor (EF). Copper presented a heterogenic distribution and higher concentrations in RG (2283.00 ± 1308.75 mg/kg) especially on the upstream downstream, associated with algicide application as well as the sediment grain size, contrary to ITU (21.81 ± 8.28 mg/kg) where a no-clear pattern of distribution was observed. Sediments in RG are predominantly categorized as “Very Bad”, whereas sediments in ITU are mainly categorized as “Good”, showing values higher than RRV. The classification is supported by the EF categorization, which in RG is primarily categorized as “Very High” contrasting to ITU classified as “Absent/Very Low”. Copper total stock in superficial sediment estimated for RG is 4515.35 Ton of Cu and for ITU is 27.45 Ton of Cu.
Keywords: Copper sulfate; Ecotoxicology; Geostatistics; Spatialization; Variogram